Differential Levels of Fatty Acid‐Amino Acid Conjugates in the Oral Secretions of Lepidopteran Larvae Account for the Different Profiles of Volatiles - Xiaoyu Ling; Shimin Gu; Caihong Tian; Huijuan Guo; Degen, Thomas; Turlings, Ted; Feng Ge; Yucheng Sun (My University, 2021)
BACKGROUND: Plants have evolved sophisticated defense responses to insect herbivore attack, which often involve elicitors in the insects' oral secretions. The major eliciting compounds in insect oral secretions across different species and their potency in inducing volatile emissions have not yet been fully characterized and compared. RESULTS: Seven lepidopteran insects with variable duration of association with maize were selected, five species known as pests for a long time (Ostrinia furnacalis, Spodoptera exigua, Spodoptera litura, Mythimna separata, and Helicoverpa armigera) and two newly emerging pests (Athetis lepigone and Athetis dissimilis). Oral secretions of the newly emerging pests have the highest total contents of Fatty Acid-Amino Acid Conjugates (FACs), and their relative composition was well separated from that of the other five species in principal compound analysis. Redundancy analyses suggested that higher quantity of FACs was mainly responsible for the increases in maize volatiles, of which (E)-3,8-dimethyl-1,4,7-nonatriene (DMNT) and (E, E)-4,- 8,12-trimethyltrideca-1,3,7,11-tetraene (TMTT) were the most strongly inducible compounds. Adding FACs to the oral secretion of S. litura larvae significantly increased the emissions of TMTT and DMNT, confirming the key role of FACs in inducing volatile emissions in maize plants. Additional experiments with artificial diet spiked with linolenic acid suggested that variation in FACs is due to differences in internal FAC degradation and fatty acid excretion. CONCLUSION: Compared with two newly emerging pests A. lepigone and A. dissimilis, the long-term pests could diminish the volatile emission by maize through reducing the FAC content in their oral secretions, which may lower the risk of attracting nat- ural enemies.